Understanding Careers Around the Globe Stories and Sourcebook - Briscoe, Jon; Dickmann, Michael; Hall, Douglas; Mayrhofer, Wolfgang; Parry, Emma (Edward Elgar Publishing, 2023)
This fascinating book comprises case studies of careers from 24 countries across the globe, highlighting culture-specific career issues, and encouraging reflection on one's own career. Interwoven with current theoretical and empirical insights from career studies, it emphasises the importance of our respective contextual settings.